2022
DOI: 10.3389/fcvm.2022.944155
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma phenylalanine and gut microbiota-derived metabolite phenylacetylglutamine in coronary in-stent restenosis

Abstract: ObjectiveThis study was designed to explore the predictive value of plasma phenylalanine (Phe) and gut microbiota-derived metabolite phenylacetylglutamine (PAGln) in coronary in-stent restenosis (ISR).MethodsPatients with coronary ISR, in-stent hyperplasia (ISH), and in-stent patency (ISP) were retrospectively enrolled in this study. Multivariable logistic regression analyses were used to identify independent risk factors of ISR. The predictive value of plasma Phe and PAGln levels was evaluated by receiver ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition, the increased levels of phenylacetyl-L-glutamine 22 , 34 , 35 , 49 , 86 , a phenylalanine derivative, was identified in the blood and urine of PD patients in five studies. Phenylacetyl-L-glutamine was derived from phenylalanine through gut microbiota by decarboxylation and then conjugated with glutamine 87 , 88 . Therefore, the increased levels of phenylacetyl-L-glutamine are highly associated with the metabolism of phenylalanine and glutamine in PD, and reflect the high activity of gut microbiota in PD patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the increased levels of phenylacetyl-L-glutamine 22 , 34 , 35 , 49 , 86 , a phenylalanine derivative, was identified in the blood and urine of PD patients in five studies. Phenylacetyl-L-glutamine was derived from phenylalanine through gut microbiota by decarboxylation and then conjugated with glutamine 87 , 88 . Therefore, the increased levels of phenylacetyl-L-glutamine are highly associated with the metabolism of phenylalanine and glutamine in PD, and reflect the high activity of gut microbiota in PD patients.…”
Section: Resultsmentioning
confidence: 99%
“…PA is an organic compound primarily produced through microbial phenethylamine metabolism by bacteria [ 34 , 35 ]. Once absorbed into the portal system, PA can be converted by the liver into phenylacetylglutamine (PAGln) [ 36 ]. A cohort study involving 1,797 female twins demonstrated an association between PAGln and the expression of the cell death activator CIDE-C, which plays a role in regulating insulin resistance in adipose tissue [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAGln has been associated with increased platelet activity and thrombosis potential [41]; recent studies point out that PAGln serum levels are correlated with coronary atherosclerosis severity and the incidence of CVD and MACE. Another study shows that high levels of PAGln are independently associated with an increased risk of coronary in-stent restenosis, which is a factor related to a worse prognosis in patients with CAD [42].…”
Section: Phenylacetylglutaminementioning
confidence: 98%